Understanding the discursive context: Production of muslim women as invisible in the written history of colonial Bengal - Chowdhury, Sanjida (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2019.